2015
DOI: 10.1039/c5cp03947a
|View full text |Cite
|
Sign up to set email alerts
|

In situ ATR-FTIR study of H2O and D2O adsorption on TiO2 under UV irradiation

Abstract: The adsorption of water and deuterium oxide on TiO2 surfaces was investigated in the dark as well as under UV(A) irradiation using in situ ATR-FTIR spectroscopy under oxygen and oxygen free conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 30 publications
3
62
0
Order By: Relevance
“…These results clearly indicate that the presence of O2 is necessary to enhance the photoadsorption of H2O and D2O on TiO2 surfaces during UV(A) irradiation. Our results confirm the critical influence of oxygen on adsorption behavior, resulting in an increase the adsorption of H2O and D2O on TiO2 surfaces which is most likely caused by a photoinduced charge transfer process [9]. Takeuchi et al proposed that when TiO2 surfaces were irradiated with UV light in the absence of O2, the electrons trapped on the Ti 3+ sites were not scavenged by O2 and the holes trapped on the TiO2 surface were immediately consumed to oxidize the lattice oxygen, resulting in the formation of oxygen vacancies.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…These results clearly indicate that the presence of O2 is necessary to enhance the photoadsorption of H2O and D2O on TiO2 surfaces during UV(A) irradiation. Our results confirm the critical influence of oxygen on adsorption behavior, resulting in an increase the adsorption of H2O and D2O on TiO2 surfaces which is most likely caused by a photoinduced charge transfer process [9]. Takeuchi et al proposed that when TiO2 surfaces were irradiated with UV light in the absence of O2, the electrons trapped on the Ti 3+ sites were not scavenged by O2 and the holes trapped on the TiO2 surface were immediately consumed to oxidize the lattice oxygen, resulting in the formation of oxygen vacancies.…”
Section: Resultssupporting
confidence: 74%
“…These results suggest that the deuteride ions show a stronger adsorption ability in the dark than hydroxyl ions at the surface of the TiO2 material. Thus, the deuteride ions could lead to an isotopic exchange process by replacing the hydroxyl groups adsorbed on the TiO2 surface (reaction 1) [9]: When the system was subsequently illuminated with UV(A) light in presence of oxygen, the amount of OH and OD group stretching increased almost immediately. These results indicate that UV irradiation leads to an increase in the number of surface OH groups which in turn increases the hydrophylicity of the TiO2 surface.…”
Section: Resultsmentioning
confidence: 99%
“…1b), an increase of the band at 3480 cm -1 was observed which could be assigned to the formation of H2O2 [20]. Conversely, as shown in figure 2b, the OH stretching band increased and shifted towards a higher wavenumber (3480 cm -1 ) during UV(A) irradiation.…”
Section: Atr-ftir Studymentioning
confidence: 81%
“…Wang et al revealed the fact that under UV(A) illumination the total exposed TiO2 surface increases due to the de-aggregation of particles agglomerates which was explained by assuming that part of the absorbed light energy is converted non-adiabatically into heat which is subsequently used to break the bonds between the particles thus producing additional surface area for the photocatalytic process [7]. Recently, we have shown that the excitation of TiO2 by UV light leads to an increase in the amount of adsorbed H2O and D2O in presence of oxygen by a photoinduced charge transfer process [20]. From this point of view the adsorption behaviour of acetate as well as the adsorption of intermediates formed during UV irradiation needs to be taken into account.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation